Physicochemical profiles of mixed ruminal microbes in response to surface tension and specific surface area - Liu, Yong; Liao, Junrui; Tang, Shaoxun; Zhou, Chuanshe; Tan, Zhiliang; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2025)
IntroductionIn ruminants, a symbiotic rumen microbiota is responsible for supporting the digestion of dietary fiber and contributes to health traits closely associated with meat and milk quality. A holistic view of the physicochemical profiles of mixed rumen microbiota (MRM) is not well-illustrated.MethodsThe experiment was performed with a 3 × 4 factorial arrangement of the specific surface area (SSA: 3.37, 3.73, and 4.44 m2/g) of NDF extracted from rice straw and the surface tension (ST: 54, 46, 43, and 36 dyn/cm) of a fermented medium in a fermentation time series of 6, 12, 24, 48 h with three experimental units. Here, we used three rumen-fistulated adult Liuyang black goats as the rumen liquid donors for this experiment.ResultsIt was found that increasing SSA decreased the average acetate/propionate ratio (A/P, p < 0.05) and increased the molarity of propionate (p < 0.05). Increasing ST decreased total volatile fatty acid (tVFA) concentration (p < 0.01). Greater SSA increased (p < 0.01) MRM hydrophobicity, whereas increasing ST increased MRM cell membrane permeability (p < 0.01). The neutral detergent fiber digestibility (NDFD, r = 0.937) and tVFA (r = 0.809) were positively correlated with the membrane permeability of MRM.DiscussionThe surface tension of the artificial medium and substrate-specific surface area had a significant influence on MRM's fermentation profiles, hydrophobicity, and permeability. The results suggest that physical environmental properties are key in regulating rumen fermentation function and homeostasis in the gastrointestinal tract ecosystem.